Breastfeeding practices of working women - V.O. Netshandama (AOSIS, 2002)
Breastfeeding is the fundamental aspect of child rearing that a woman copes with. It creates a wonderful bond between mothers and their babies. The importance of breast feeding to child health is highlighted by the yearly World Breastfeeding week (Forste, Weiss & Lippincott 2001:291). Breastfeeding promotions in the Northern province like anywhere else in the country appear effective and visible enough to encourage women at all levels to breastfeed. Ironically, many women give up breastfeeding when they return to work because the thoughts of expressing their milk at work and the fiddling around with pumps and storage at work seem overwhelming (McAlpine 1998:80). Based on the assumption that breastfeeding requires commitment and determination, the researcher thought it was necessary to enquire about the experiences of working women on breastfeeding. Focus group interviews were conducted using a semi-structured format. Twenty-six women participated in three focus group discussions. The study was conducted in the suburban areas of the Northern Province, Soutpansberg region. Data was transcribed from a taped session and analysed using an open code method.